Studies of the Torrefaction of Sugarcane Bagasse and Poplar Wood (2017)
In this thesis, the main physical and chemical characteristics of sugarcane bagasse and poplar wood submitted to a thermo-chemical torrefaction process were studied. The materials were dried at a temperature of 105°C for 12 hours, to a moisture content of about 5%. The sugarcane bagasse was torrefied in TGA and in a custom designed thermogravimetric reactor for the evaluation of big particles in the temperature ranges of 200-300°C. With TGA tests, kinetic parameters representative of the material decomposition were obtained, and with large particles tests, the degradation was compared when the amount and particle size of material increases. The products of all torrefied tests were characterized and compared. Poplar wood was torrefied in a custom thermogravimetric reactor in order to determine its kinetic parameters and in a two-stage rotary reactor by varying the operating parameters. These experimental tests with poplar were carried out in the circulating fluidized bed laboratory of Dalhousie University, Halifax, Canada. In the rotary reacctor, the biomass is dried in the first stage, and then torrefied in the second. Torrefaction process is carried out under volatiles atmosphere generated during the process, without inlet of inert gases. Fine particles, between 0.5 and 1 mm in diameter were used in this study, and characterized before and after torrefaction. A characterization of the biomass being torrefied was performed using two novel scooper devices for sample capture from inside reactor, specially designed for this research. These two devices allow to capture biomass samples being torrefied and measuring their temperatures in different axial positions of the reactor. Two phenomenological models were constructed: a two-dimensional model for torrefaction of a biomass particle and a two-stage rotary reactor model. Both were duly validated and great information was obtained from them. A kinetic scheme involving secondary reactions to the interior of the biomass particle was used and validated with experimental information. Four phases were considered in the model: Biomass, water, char and gases, and for each of them it was possible to obtain distributions of their volumetric fractions at any time in the process. In addition, temperature distributions, velocities of volatiles generated and pressures can be obtained. A vertical reactor was designed and built in order to evaluate the behavior of large particles in torrefaction process. With this reactor, it is possible to follow the mass and temperature of the particle during the process. In addition, it is possible to capture volatiles and separate them into condensables and non-condensables throught a condensation unit which operates at -15°C and capture the condensable portion of the volatiles stream. With this reactor, it is possible to perform a complete characterization of all torrefation products such as liquid, gas and solid. This reactor was designed and built by the TAYEA group, specifically for the realization of this research work.